2009
DOI: 10.1182/blood-2008-08-174508
|View full text |Cite
|
Sign up to set email alerts
|

DLL1-mediated Notch activation regulates endothelial identity in mouse fetal arteries

Abstract: Notch signaling has been shown to regulate various aspects of vascular development. However, a specific role of the ligand Delta-like 1 (DLL1) has not been shown thus far. Here, we demonstrate that during fetal development, DLL1 is an essential Notch ligand in the vascular endothelium of large arteries to activate Notch1 and maintain arterial identity. DLL1 was detected in fetal arterial endothelial cells beginning at embryonic day 13.5. While DLL4-mediated activation has been shown to suppress vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
355
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(364 citation statements)
references
References 52 publications
(63 reference statements)
9
355
0
Order By: Relevance
“…S1) using an inducible Cre-loxP system. We used the Cdh5(PAC)-CreER T2 transgene for CreER T2 expression in ECs (Sorensen et al, 2009;Wang et al, 2010). We bred Cdh5(PAC)-CreER T2 ; Rbpj flox/flox mice, administered Tamoxifen (TAM) at postnatal day (P) 1 and P2, and harvested tissue at P14 (hereafter referred to as immature Rbpj iΔEC ).…”
Section: Endothelial Deletion Of Rbpj From Birth Results In Av Shuntsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1) using an inducible Cre-loxP system. We used the Cdh5(PAC)-CreER T2 transgene for CreER T2 expression in ECs (Sorensen et al, 2009;Wang et al, 2010). We bred Cdh5(PAC)-CreER T2 ; Rbpj flox/flox mice, administered Tamoxifen (TAM) at postnatal day (P) 1 and P2, and harvested tissue at P14 (hereafter referred to as immature Rbpj iΔEC ).…”
Section: Endothelial Deletion Of Rbpj From Birth Results In Av Shuntsmentioning
confidence: 99%
“…Mouse lines: Cdh5(PAC)-CreER T2 (Sorensen et al, 2009), Rbpj flox (Tanigaki et al, 2002), Rosa26 mT/mG (Muzumdar et al, 2007), Coup-TFII flox-nlacZ (Takamoto et al, 2005), Efnb2 tau-lacZ (Wang et al, 1998) and Ephb4 tau-lacZ (Gerety et al, 1999) were kindly provided by Ralf Adams (Max Planck Institute for Molecular Biomedicine, Münster, Germany), Tasuku Honjo (Kyoto University, Japan), Liqun Luo (Stanford University School of Medicine, Stanford, CA, USA), Sophia Tsai (Baylor College of Medicine, Houston, TX, USA), and, the latter two, by David Anderson (California Institute of Technology, Pasadena, CA, USA), respectively. 100 μg TAM (Sigma) in 50 μl peanut oil (Planters) was injected into stomach at P1 and P2.…”
Section: Micementioning
confidence: 99%
“…In ECs, Notch (Notch1, 4) activation can be induced by various Notch ligands, including Dll1, Dll4, and Jagged2, expressed in arterial ECs, and Jagged1 expressed in ECs and mural cells. 35, 36 All of this Notch signaling is considered to be mediated by the Notch intracellular domain (NICD) and RBP-J transcription factor (also called CSL, CBF-1 in mammals, Suppressor of Hairless [Su(H)] in Drosophila and LAG-1 in Caenorhabditis elegans). Genetic animal studies of the Notch signal related-genes have shown that Notch1 and 4, Dll4, RBP-J, and Hey1/Hey2 are essential for arterial formation in the developing vasculature.…”
Section: Roles Of Notch Signaling In Artery Formationmentioning
confidence: 99%
“…17 With the aim of developing a more reproducible model of AVM formation, and bypassing embryonic lethality of the endoglin null mouse, we have taken a conditional knockout approach combining our recently generated endoglin-floxed mouse model 18 with an endothelial specific Cdh5(PAC)-Cre ERT2 transgenic line. 19 As Cre ERT2 is inactive until exposed to tamoxifen, this combination of alleles allows endoglin depletion in ECs at different stages of development and adult life, permitting a high degree of manipulability with which to investigate the role of endoglin in vivo. 2fl/2fl and included both tamoxifen-treated and tamoxifen-untreated groups.…”
mentioning
confidence: 99%